The Challenge of Women's Inclusion for Novel Teachers. Case Study in a Teacher Educator Public University - Marolla-Gajardo, Jesús (Frontiers in Education, 2020)
The following article is about the conceptions that different novel teachers of history and social sciences have concerning the inclusion of women and their history during their teaching practices. The objectives followed were to interpret and understand the content of the discourse of the interviewees, in order to analyse the advantages and limitations that the participants recount about their initial teaching practices. The methodology used is qualitative, forming a focus group and interviewing the teachers. Amongst the main results, it stands out that the formation given has not included women and their history, confined in traditional perspectives with predominance of powerful men. The interviewees add that in their teaching practice they have not worked with women’s narrative, however; they recognise how relevant it is to include and transform teaching practices based on the recognition of gender issues in today’s world. From a history and social sciences teaching point of view, learning and working with the relevance of actions and narratives of women would generate agency. Thus, students could feel empower themselves by identifying themselves with these new models ; this with the objective of generating social change concerning gender equality.